2020
DOI: 10.2196/preprints.20988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital Information Technology Use, Self-Rated Health, and Depression: Population-Based Analysis of a Survey Study on Older Migrants (Preprint)

Abstract: BACKGROUND Previous studies have found that in general, in older adults, poor health is associated with a lower likelihood of Internet use, but it is not well known how different indicators of health are associated with different types of digital information technology (DIT) use. Moreover, little is known about the relationship between health and the types of DIT use in older ethnic minority and migrant populations. O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Modern research shows that depression and low self-esteem of health are associated with less social involvement and decreased interest in current events, less frequent use of Internet resources and social networks in communication [11]. Meanwhile, in previous works, we have shown that social isolation repeats the trends in affective states in Russia, and is an independent predictor of cardiovascular events [12,13].…”
Section: Discussionmentioning
confidence: 76%
“…Modern research shows that depression and low self-esteem of health are associated with less social involvement and decreased interest in current events, less frequent use of Internet resources and social networks in communication [11]. Meanwhile, in previous works, we have shown that social isolation repeats the trends in affective states in Russia, and is an independent predictor of cardiovascular events [12,13].…”
Section: Discussionmentioning
confidence: 76%